The R740S mutation in the V‐ATPase a3 subunit increases lysosomal pH, impairs NFATc1 translocation, and decreases in vitro osteoclastogenesis. (18th December 2012) - Voronov, Irina; Ochotny, Noelle; Jaumouillé, Valentin; Owen, Celeste; Manolson, Morris F; Aubin, Jane E
Abstract: Vacuolar H + ‐ATPase (V‐ATPase), a multisubunit enzyme located at the ruffled border and in lysosomes of osteoclasts, is necessary for bone resorption. We previously showed that heterozygous mice with an R740S mutation in the a3 subunit of V‐ATPase (+/R740S) have mild osteopetrosis resulting from an ∼90% reduction in proton translocation across osteoclast membranes. Here we show that lysosomal pH is also higher in +/R740S compared with wild‐type (+/+) osteoclasts. Both osteoclast number and size were decreased in cultures of +/R740S compared with +/+ bone marrow cells, with concomitant decreased expression of key osteoclast markers (TRAP, cathepsin K, OSCAR, DC‐STAMP, and NFATc1), suggesting that low lysosomal pH plays an important role in osteoclastogenesis. To elucidate the molecular mechanism of this inhibition, NFATc1 activation was assessed. NFATc1 nuclear translocation was significantly reduced in +/R740S compared with +/+ cells; however, this was not because of impaired enzymatic activity of calcineurin, the phosphatase responsible for NFATc1 dephosphorylation. Protein and RNA expression levels of regulator of calcineurin 1 (RCAN1), an endogenous inhibitor of NFATc1 activation and a protein degraded in lysosomes, were not significantly different between +/R740S and +/+ osteoclasts, but the RCAN1/NFATc1 ratio was significantly higher in +/R740S versus +/+ cells. The lysosomal inhibitor chloroquine significantly increased RCAN1 accumulation in +/+ cells, consistent with the hypothesis that higher lysosomal pH impairs RCAN1 degradation, leading to a higher RCAN1/NFATc1 ratio and consequently NFATc1 inhibition. Our data indicate that increased lysosomal pH in osteoclasts leads to decreased NFATc1 signaling and nuclear translocation, resulting in a cell autonomous impairment of osteoclastogenesis in vitro. © 2013 American Society for Bone and Mineral Research